MODELING OF CRYSTAL FIELD PARAMETERS AND ENERGY LEVELS SCHEME SIMULATION FOR Fe⁶⁺ DOPED IN K₂MO₄ (M= Cr, S, Se) - BRIK, M. G.; ANDREICI, E. -L.; AVRAM, N. M. (Studia Universitatis Babeș-Bolyai Physica, 2015)
In this paper we report the results of a detailed comparative crystal field analysis of the crystal field parameters and energy level schemes, for all three above mentioned materials. The crystal structure data was used to calculate the crystal field parameters in the framework of exchange charge model using the Symmetry Adapted Axis System centered at the impurity ion. A thorough consideration of the impurity center symmetry was performed and the calculated crystal field parameters were used to diagonalize the crystal field Hamiltonian for each system. Energy levels obtained in this way were compared with the corresponding experimental data to yield good agreement between the theoretical and experimental results.